2006
DOI: 10.1590/s0044-59672006000300014
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of the foregut of larvae and postlarva of Sesarma curacaoense De Man, 1892: a species with facultative lecithotrophy during larval development

Abstract: Previous study on the resistance of larvae of Sesarma curacaoense submitted to starvation has revealed a facultative lecithotrophy during zoeal stages, but megalopa and first juvenile stages are exclusively feeding stages. In the present study, the gross morphology and fine structure of the foregut of S. curacaoense were investigated during larval, megalopa and first juvenile stages. The foregut of the zoea I show specific setae and a filter press apparently functional. The foregut undergoes changes in the zoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…However, they have a facultative lecithotrophic development because they are feeding animals if foods are available in the environment. This observation was supported by Melo et al (2006) who reported presence of numerous setae in the cardiopyloric valve and a complex and specialized filter press in the foreguts of S. curacaoense larvae.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, they have a facultative lecithotrophic development because they are feeding animals if foods are available in the environment. This observation was supported by Melo et al (2006) who reported presence of numerous setae in the cardiopyloric valve and a complex and specialized filter press in the foreguts of S. curacaoense larvae.…”
Section: Discussionsupporting
confidence: 61%
“…However, despite of a visible specialization of the filter press, few morphological changes occur during the development of the zoeal stomachs (Fig. 5a,b) compared to those zoeal stages previously reported (Abrunhosa et al, 2003;Melo et al 2006;Lima et al, 2005). These observations strongly suggest that no functionality also occurs in the foregut during all zoeal development.…”
Section: Discussionmentioning
confidence: 48%
“…The grapsids S. curacaoense (described by Melo et al, 2006) and S. rectum (present study) show morphologic similarity in the foregut from larval to the juvenile stages. Both species hold specific setae in the cardiopyloric valve and filter press, which is characteristic of most decapod zoeae.…”
Section: Discussionmentioning
confidence: 48%
“…The most significant ontogenic change in the stomach of M. brachydactyla occurs during the molt to megalopa, a transitional stage between the pelagic zoea and the benthic juvenile (Anger, 2001). We observed that the transformation of the stomach includes the appearance of the ossicle system, cardiac sacs, and gastric mill teeth, which also occurs in other brachyurans (Abrunhosa & Melo, 2008;Abrunhosa, Melo, & Abrunhosa, 2003;Abrunhosa, Simith, Monteiro, de Souza Junior, & Oliva, 2011;Jantrarotai & Sawanyatiputi, 2005;Lumasag, Quinitio, Aguilar, Baldevarona, & Saclauso, 2007;Melo, Abrunhosa, & Sampaio, 2006). The cuticle of the newly formed ossicles and gastric mill teeth differs from the cuticle of the previous zoeal stages and the cuticle of other stomach structures as the cardiac sacs.…”
Section: Discussionmentioning
confidence: 71%